An investigation of soccer ball velocity on instep kick with and without arm swaying - Chen, Y.; Chang, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Many biomechanical researches of soccer try to understand the kinematic and kinetic effects of kicking; the most widely concerned is maximal force instep kick (powerful instep kick). Kellis and Katis (2008) reported that the ball velocity in instep kick on related researches were surpass in 72 Km/h (20m/s), and the highest was 115.6 Km/h (32.1 m/s). The higher ball speed, the lower time a keeper react. The kicking skills are complicated, and multiple factors must be measured. Not only lower limbs involve on kicking task, but also upper body affects the kicking performance. Kicking with arm swaying is a common motion in goal kick, directly free kick, penalty kick, and instep kick. The arm (non-kicking side) begins to sway when a player run-up to kick a ball at the last step and it may provide more strength to kick a ball. Arm swaying motion also applies in other sports. It advances the jumping performances in standing long jump due to maintaining balance and increasing the velocity of the body's center of gravity (Ashby & Heegaard, 2002). The muscle pre-lengthening and stretch by arm swaying increased the strength of kicking; skilled soccer players had significantly larger knee flexion-extension movement (Shan and Westerhoff, 2005). The range of motion (ROM) of knee and the foot segment velocity are the important parameter for understanding the skill of players. The distance between right ankle and left ankle (while the support-foot landing) was measure to understand the hip and body stretch, and this distance affect the time of acting force for kicking the ball. To improve the ball velocity on kicking, the purpose of this study was to compare the ball velocity and kinematic data on different motions of arm. The motions were arm swaying and arm fixed (without arm swaying) while kicking the ball. The results were a useful reference for soccer players and instructors.